INCOME DIFFERENCES SHG MEMBER IN THE VILLAGE SURIAN DISTRICT OF SOLOK REGENCY MIRROR COST BEFORE And AFTER GETTING LOAN REVOLVING PNPM-MANDIRI RURAL - -, Yuanita - (Pendidikan Ekonomi, 2014)
This research has a background by income from society in kanagarian Kenagarian Surian, Kecamatan Pantai Cermin, Kabupaten Solok . It is caused by capiital deficiency of society. The research aims to know any diffrencess income of KSM members before dan after recieving debit capital from PNPM-MP Kenagarian Surian Kecamatan Pantai Cermin Kabupaten Solok. Based on result of analyze data got the income before geting debit capital mean score was IDR. 1.001.298,7 and income after geting debit capital mean score was IDR. 1301298,7. Then, hyphothesis testing was used Z test by using SPSS 15.0 version, got the score of Z calculate -7564 smallest that table Z -1,992 wich mean that hyphothesis was accepted on the real significant Î± (0,05). It was concluded that there is diffrences between income before getiing debit capital with income after getiing debit capital from PNPM-MP at Kenagarian Surian Kecamatan Pantai Cermin Kabupaten Solok